Paper : Asteroseismic Properties of Solar-type Stars Observed with the NASA K2 Mission: Results from Campaigns 1–3 and Prospects for Future Observations. (8th November 2016) - Lund, Mikkel N.; Chaplin, William J.; Casagrande, Luca; Aguirre, Víctor Silva; Basu, Sarbani; Bieryla, Allyson; Christensen-Dalsgaard, Jørgen; Latham, David W.; White, Timothy R.; Davies, Guy R.; Huber, Daniel; Buchhave, Lars A.; et al.
Abstract: We present an asteroseismic analysis of 33 solar-type stars observed in short cadence (SC) during Campaigns (C) 1–3 of the NASA K2 mission. We were able to extract both average seismic parameters and individual mode frequencies for stars with dominant frequencies up to ∼3300 μ Hz, and we find that data for some targets are good enough to allow for a measurement of the rotational splitting. Modeling of the extracted parameters is performed by using grid-based methods using average parameters and individual frequencies together with spectroscopic parameters. For the target selection in C3, stars were chosen as in C1 and C2 to cover a wide range in parameter space to better understand the performance and noise characteristics. For C3 we still detected oscillations in 73% of the observed stars that we proposed. Future K2 campaigns hold great promise for the study of nearby clusters and the chemical evolution and age–metallicity relation of nearby field stars in the solar neighborhood. We expect oscillations to be detected in ∼388 SC targets if the K2 mission continues until C18, which will greatly complement the ∼500 detections of solar-like oscillations made for SC targets during the nominal Kepler mission. For ∼30–40 of these, including several members of the Hyades open cluster, we furthermore expect that inference from interferometry should be possible.